Indicators of Scholarly Production and Impact of Faculty Members at some State Universities in Sudan: An Analytical Study - Awad Allah Mohammed Abu Elgassim Mohamme; Abdallah Hussein Abdallah Hamd (University of Science and Technology, Yemen, 2017)
The purpose of this study was to investigate the level of scholarly production and impact indicators of faculty members at some state Universities in Sudan. The study used a purposive sample which consisted of (191) faculty members from state Universities (El Imam El Mahdi, Bakhat El rrida, Kordofan, & West Kordofan University). To achieve the objectives of the study, the researcher used CVs and content analysis as well as the descriptive analytical method. The study showed that the level of indicators of production and scholarly impact of faculty members at those state Universities was low, as the mean was (6.524). The mean of scholarly impact was (7.952) at a level (0.05). There was also a difference in the scholarly production and impact indicators of faculty members at those state Universities in Sudan depending on the place of obtaining the doctorate degree, in favour of those who did their degrees abroad. Also, there was a difference in the scholarly production and impact indicators depending on the academic rank (assistant professor, associate professor, and professor), in favour of Professors. Based on the study results it was recommended that the university administrations and the ministry of higher Education should provide appropriate opportunities for researchers to publish their studies and to subscribe to international academic networks that are interested in the impact of research. Keywords: H-Index, Scholarly production, Scholarly impact.